Effects of Glucomannan-Enriched, Aronia Juice-Based Supplement on Cellular Antioxidant Enzymes and Membrane Lipid Status in Subjects with Abdominal Obesity - Nevena Kardum; Gordana Petrović-Oggiano; Marija Takic; Natalija Glibetić; Manja Zec; Jasmina Debeljak-Martacic; Aleksandra Konić-Ristić (The Scientific World Journal)
The aim of this study was to analyze the effects of a 4-week-long consumption of glucomannan-enriched, aronia juice-based supplement on anthropometric parameters, membrane fatty acid profile, and status of antioxidant enzymes in erythrocytes obtained from postmenopausal women with abdominal obesity. Twenty women aged 45–65 with a mean body mass index (BMI) of 36.1 ± 4.4 kg/m2 and waist circumference of 104.8 ± 10.1 cm were enrolled. Participants were instructed to consume 100 mL of supplement per day as part of their regular diet. A significant increase in the content of n-3 (P<0.05) polyunsaturated fatty acids in membrane phospholipids was observed, with a marked increase in the level of docosahexaenoic fatty acid (P<0.05). Accordingly, a decrease in the n-6 and n-3 fatty acids ratio was observed (P<0.05). The observed effects were accompanied with an increase in glutathione peroxidase activity (P<0.05). Values for BMI (P<0.001), waist circumference (P<0.001), and systolic blood pressure (P<0.05) were significantly lower after the intervention. The obtained results indicate a positive impact of tested supplement on cellular oxidative damage, blood pressure, and anthropometric indices of obesity.